Entropic Contributions to Protein Stability. Issue 7 (16th June 2020) - Bigman, Lavi S.; Levy, Yaakov
Abstract: Thermodynamic stability is an important property of proteins that is linked to many of the trade‐offs that characterize a protein molecule and therefore its function. Designing a protein with a desired stability is a complicated task given the intrinsic trade‐off between enthalpy and entropy which applies for both the folded and unfolded states. Traditionally, protein stability is manipulated by point mutations which regulate the folded state enthalpy. In some cases, the entropy of the unfolded state has also been manipulated by means that drastically restrict its conformational dynamics such as engineering disulfide bonds. In this mini‐review, we survey various approaches to modify protein stability by manipulating the entropy of either the unfolded or the folded states. We show that point mutations that involve elimination of long‐range contacts may have a greater destabilization effect than mutations that eliminate shorter‐range contacts. Protein conjugation can also affect the entropy of the unfolded state and thus the overall stability. In addition, we show that entropy can contribute to shape the folded state and yield greater protein stabilization. Hence, we argue that the entropy component can be practically manipulated both in the folded and unfolded state to modify protein stability. Abstract :